Pengaruh Kepemilikan Manjerial, Kebijakan Hutang, Profitabilitas, Ukuran Perusahaan, dan Kesempatan Investasi terhadap Kebijakan Dividen pada Perusahaan Manufaktur yang Terdaftar pada Bursa Efek Indonesia - Hairudin Hairudin; Andri Eka Yunindra; Fadel Fatur Rahman (Business and Enterpreneurship Journal (BEJ), 2020)
Manufacturing companies in an effort to maintain reputation in the eyes of investors always distribute dividends to shareholders. The problem of managerial ownership influence, debt policy, profitability, company size and investment opportunities. The hypothesis is whether managerial ownership, debt policy, profitability, company size, and investment opportunities influence the company's dividend policy. Calculation results show that X1, X2, X3, X4, and X5 together have no effect on Y, the hypothesis is accepted, as evidenced by the test (F) where the significance value of 0.188 0.05. While for the test (tcount) X4 has a positive and significant effect on Y. With a tcount